Pengaruh Gratis Ongkos Kirim, Diskon Dan Iklan Shopee Terhadap Keputusan Pembelian Konsumen (Studi Kasus Pada Mahasiswa Universitas Islam Malang FEB Angkatan 2019) - Afifuddin, Muhammad; Basalamah, Muhammad Ridwan; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to assess the impact of free shipping (X1), discounts (X2), and Shopee ads (X3) on purchasing decisions (Y) among Economics and Business Faculty students at the Islamic University of Malang. The research utilizes an explanatory approach with a quantitative method. Data collection involved distributing questionnaires via Google Form to 100 eligible respondents. Analysis was conducted using multiple linear regression techniques. The findings indicate that free shipping, discounts, and Shopee ads individually (t-test) positively influence purchasing decisions. Collectively (F-test), these variables also positively impact purchasing decisions. The R-squared value reveals that 33.7% of the variation in purchasing decisions can be attributed to free shipping, discounts, and Shopee ads. The remaining variation is influenced by undisclosed factors. In conclusion, the strategies involving free shipping, discounts, and Shopee ads significantly affect purchasing decisions, particularly among students at the Economics and Business Faculty of the Islamic University of Malang. Keywords: Free Shipping, Discounts, Shopee Advertisements, and Purchase Decisions